Analisis Sistem Informasi Akuntansi Penerimaan Kas Pada Dinas Perdagangan dan Perindustrian Kab. Langkat - Oktania, Mila; Rokan, Mustapa Khamal; Kusmilawaty, Kusmilawaty (Ekonomi Bisnis Manajemen dan Akuntansi (EBMA), 2023)
Department of Trade and Industry District. Langkat is an element the implementation of local government in the field of trade and industry led by a Head of Service. In carrying out its activities, Information regarding the description of an agency can be assessed from agency accounting the . In accounting activities, of course, guidelines or internal references are needed carry out their activities. This study aims to determine the application cash receipts accounting information system at the Department of Trade and District Industry Langkat. This type of research is qualitative in nature descriptive. The type of data used in this study is the type of data qualitative with data collection techniques carried out using observation, documentation and interviews. The results of this study indicate that cash receipts accounting information system carried out at the Department Trade and Industry Kab. Langkat still not showing discrepancy. The functions, the documents that are generated, the notes that used and cash receipts procedures are not in accordance with the existing theory only a few fit the existing theory. Application of information systems accounting carried out at the Department of Trade and Industry of Kab. Langkat consists of the procedures that make up the cash receipts system, documents and records used, related functions and has been has internal control in the process of monitoring the accounting system cash receipts.